CODE MIXING DEBAT CAPRES CAWAPRES 2014 - Yuli Astutik (Kanal: Jurnal Ilmu Komunikasi, 2014)
The aims of this research are to identify the typeof code mixingon debate of president and vice president candidates and to know the types of code mixing process and also to investigate the elements of English which appear in code mixing on debate of president and vice president candidates 2014 in Indonesia. The method used in this research is descriptive qualitative because the data are in the form of words not in the form of numbers. The instruments used in this research is observation, the writer uses non-participant observation because the writer is not directly involved in the activities. In order to obtain an accurate and valid data, the writer recorded the source of data. The results of this research show that the type of code mixing found in this research is outer code mixing because the Indonesia language mixed with English. Besides,it is found that there are three types of code mixing process in the utterances; insertion, alternation, and congruent lexicalization. In this research also found the English code mixing elements, such as Word 186 (94, 89%), Phrase 107 (54,59%) and Clause 1 (0.51 %).